2014
DOI: 10.1007/s10072-014-1642-7
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with craniocervical dystonia: Italian validation of the “Cervical Dystonia Impact Profile (CDIP-58)” and the “Craniocervical Dystonia Questionnaire (CDQ-24)”

Abstract: Dystonia is a disabling and disfiguring disorder that can often affect many aspects of patients' daily lives, and lower their self-esteem. To date, quality of life (QoL) has been assessed in dystonic patients using generic measures that do not address the specific problems of this diagnostic group. Recently, two disease-specific scales "The Cervical Dystonia Impact Profile (CDIP-58)" and the "Craniocervical Dystonia Questionnaire (CDQ-24)" were validated for measuring QoL in craniocervical dystonia patients. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Because we observed that subjects with total score near the bottom or the top of the scale did not exceed 15% in either scale formulation, we could rule out the possibility of floor or ceiling effects. Our analysis found a partial correlation between both versions of the scale and the JRS, or the quality of life (QoL) scale CDQ‐24 . The scale presented here explores domains that are not considered in the prior scales: estimation of spasm severity is present in the JRS but not in the CDQ‐24, whereas spasm‐associated features are not considered in the JRS but may contribute to QoL assessment by the CDQ‐24.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Because we observed that subjects with total score near the bottom or the top of the scale did not exceed 15% in either scale formulation, we could rule out the possibility of floor or ceiling effects. Our analysis found a partial correlation between both versions of the scale and the JRS, or the quality of life (QoL) scale CDQ‐24 . The scale presented here explores domains that are not considered in the prior scales: estimation of spasm severity is present in the JRS but not in the CDQ‐24, whereas spasm‐associated features are not considered in the JRS but may contribute to QoL assessment by the CDQ‐24.…”
Section: Discussionmentioning
confidence: 85%
“…Our analysis found a partial correlation between both versions of the scale and the JRS, 11 or the quality of life (QoL) scale CDQ-24. 16,17 The scale presented here explores domains that are not considered in the prior scales: estimation of spasm severity is present in the JRS 11 but not in the CDQ-24, 16,17 whereas spasm-associated features are not considered in the JRS but may contribute to QoL assessment by the CDQ-24. Comparison of total severity scores at baseline and 4 weeks after BoNT treatment highlighted the sensitivity to change of both versions of the scale.…”
Section: Discussionmentioning
confidence: 99%
“…TWSTRS showed good reliability in all the subscales, with bigger variability depending on the gravity of disease. Disability subscale is more sensitive than the subscales for pain and for severity of the disease as well 4,23 .…”
Section: Tablementioning
confidence: 95%
“…Inter-test reliability was good, but the validity of this scale was not studied. Cervical Dystonia Impact Profile (CDIP-58) measures the 58 health parameters in CD, but it has not been widely used in investigations 4,23 .…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation